Factors influencing self-efficacy for self-management among adult people with human immune deficiency virus on antiretroviral therapy in public hospitals of south-west Ethiopia - Abdisa, MisganaTesgera; Gindaba, Bekan Gudeta; Zerihun, Ebisa (Frontiers in Psychology, 2024)
Introduction: Self-management is crucial for effective HIV management, and self-efficacy is a mechanism for achieving it, but there is limited evidence on variables that affect self-efficacy. This study aimed to identify factors influencing self-efficacy for self-management among aimed to adults on antiretroviral therapy in resource constraint settings.: A cross-sectional study was conducted among 422 adult people on antiretroviral therapy in southwest Ethiopia from March to April 2022. Face-to-face interviews were used to gather data using a structured questionnaire on the self-efficacy measure. The data were then imported into Epi Data version 4.2 and exported to SPSS version 26. Descriptive statistics, independent tests, oneway analysis of variance, Pearson correlation, and multivariate linear regression was used to analyze the data. The predictors with p-value less than 0.05 were declared statistically significant.Results: A total of 413 adults on antiretroviral therapy were interviewed with response rate of 97.9%. The total mean score of self-efficacy for self-management was 15.12 (± 2.22) out of a total of 24. Higher age, gender of the female, divorced, duration of diagnosis and drug side effects was negatively predictors of low self-efficacy. Higher schooling, urban residence, better income, and the use of reminders were positively influencing self-efficacy for self-management.The study found low self-efficacy among adults on antiretroviral therapy and higher age, female gender, HIV duration, and presence of drug side effects were associated with lower self-efficacy, while higher schooling, better income, and use of reminder use were associated with higher self-efficacy for self-management. Further research is needed to determine the causal relationship between these variables and self-efficacy.